Pendampingan Penulisan Karya Ilmiah Penyuluhan Agama Kementerian Agama Kota Mojokerto dalam Suksesi Program Penyuluhan Agama Award 2024 - Ridlo, Miftakhur; Khanif, Abdullah (Universitas Nahdlatul Ulama Sidoarjo, 2024)
This article discusses assistance in writing scientific work for Religious Counselors at the Ministry of Religion of Mojokerto City, which was held on 13 – 14 May 2024 with a total of 27 people. Scientific writing is writing that discusses a problem based on the results of investigations, observations, data collection obtained from research (in the field or in the laboratory) or literature review which is based on logical and empirical scientific thinking (methods). Religious instructors have an important role in providing religious guidance to the community. The 2024 Religious Counselor Award is the right momentum to appreciate and encourage increasing the capacity of religious counselors in this matter. Therefore, this scientific writing assistance program was held to facilitate and guide religious instructors so that they can produce quality scientific papers. This mentoring methodology is carried out through several stages, namely: Basic Training: Providing basic training regarding scientific writing techniques, use of references, and the structure of scientific writing. Intensive Guidance: Provide intensive guidance through individual and group consultation sessions, discussing concepts, methodology and data analysis. Periodic Evaluation: Conduct periodic evaluations of the development of scientific papers being prepared by religious instructors. Completion of Work: Providing final input and corrections to improve scientific papers before submitting them in competitions. The activity of assisting scientific writing for religious instructors at the Mojokerto City Ministry of Religion is part of strengthening careers and performance which will later be prepared for the Extension Counselor Award level in 2024. From this mentoring process, religious instructors are expected to be able to strengthen soft and hard skills in the field of writing scientific papers